4
$\begingroup$

Let $f:\mathbb{R}\to \mathbb{R}$ such $f(x)$ at $x=0$ continuous, and for any $x,y\in \mathbb{R}$ such $$f(x+2f(y))=f(x)+y+f(y)$$ Find $f(x)$.

Let $x=0,y=0$ then we have $$2f(2f(0))=f(0)++f(0)$$ Let $y=2f(0)$ then we have $$f(x+2f(2f(0))=f(x)+2f(0)+f(2f(0))$$ so we have $$f(x+4f(0))=f(x)+4f(0)$$ on the other hand we have $$f(x+4f(0))=f(x+2f(0))+0+f(0)=2f(0)+f(x)$$ so we have $f(0)=0$ Then I can't deal with this problem

$\endgroup$
5
  • $\begingroup$ Maybe I am off base but what happens if you plug in $y=x$? $\endgroup$ Sep 23, 2016 at 5:29
  • 1
    $\begingroup$ @CameronWilliams you get that $x+2f(x)$ is a fixed point. $\endgroup$
    – CryoDrakon
    Sep 23, 2016 at 5:30
  • $\begingroup$ Am I missing something or does $f(x)=x$ work? $\endgroup$
    – Mastrem
    Sep 23, 2016 at 6:21
  • 1
    $\begingroup$ @Mastrem It does, but presumably the question is to find all such functions. $\endgroup$
    – stewbasic
    Sep 23, 2016 at 6:22
  • 1
    $\begingroup$ @Mastrem it works, but no one says this equation has only one solution. You have to prove then that it's the only one. $\endgroup$
    – CryoDrakon
    Sep 23, 2016 at 6:23

2 Answers 2

6
$\begingroup$

Substitute $x\mapsto y$ to get $$ f(y+2f(y))=y+2f(y). $$ Now substitute $y\mapsto y+2f(y)$: $$ f(x+2f(y+2f(y)))=f(x)+y+2f(y)+f(y+2f(y)). $$ Thus $$ f(x+2y+4f(y))=f(x)+2y+4f(y). $$ Substituting $x\mapsto x+2y+2f(y)$, $$ f(x+2y+4f(y))=f(x+2y+2f(y))+y+f(y). $$ Substituting $x\mapsto x+2y$, $$ f(x+2y+2f(y))=f(x+2y)+y+f(y). $$ Combining the last 3 equations, $$ f(x+2y)=f(x)+2f(y). $$ Thus $$ f(x)=f(0+2x/2)=f(0)+2f(x/2)=2f(x/2), $$ so $$ f(x+y)=f(x+2y/2)=f(x)+2f(y/2)=f(x)+f(y). $$ Since you are given that $f$ is continuous at $0$, it must be continuous everywhere. Now there is a standard argument to show that $f(x)=f(1)x$ (prove it on rationals and extend by continuity). Finally using the original equation, we see $f(1)=1$ or $-\frac12$, so the solutions are $f(x)=x$ or $f(x)=-x/2$.

$\endgroup$
3
$\begingroup$

Setting $x=y$ gives $f(x+2f(x))=x+2f(x)$, and so $f(y)=y$ whenever $y$ is of the form $x+2f(x)$ for some $x$. Note also that if $f(y)=y$, then for any $x$, $f(x+2y)=f(x)+2y$.

Now consider the function $g(x)=f(x)-x$. From the previous paragraph, we see that if $f(y)=y$ then $g(x+2y)=g(x)$. In particular, every number of the form $2x+4f(x)$ is a period of $g$. Let $P\subseteq\mathbb{R}$ be the group of periods of $g$, i.e. the set of $p$ such that $g(x)=g(x+p)$ for all $x$. There are now two cases.

The first case is that $P$ is not cyclic. Then $P$ is dense in $\mathbb{R}$, and so each coset of $P$ is dense in $\mathbb{R}$, and in particular $0$ is in the closure of each coset. But by definition of $P$, $g$ is constant on each coset of $P$, and so by continuity of $g$ at $0$ this constant value must be equal to $g(0)$. Thus $g(x)=g(0)$ for all $x$, and $g$ is constant everywhere. Thus $f(x)$ has the form $f(x)=x+c$ for some constant $c$. Plugging this into the functional equation gives $$x+2(y+c)+c=x+c+y+y+c,$$ so $c=0$. Thus $f(x)=x$.

The second case is that $P$ is cyclic, generated by some $p\in\mathbb{R}$ (possibly $0$). Then every number of the form $2x+4f(x)$ is an integer multiple of $p$. But $2x+4f(x)$ is continuous at $0$, so this means $2x+4f(x)$ is constant in a neighborhood of $0$. As you've shown, $f(0)=0$, so $2x+4f(x)=0$ for all $x$ in some neighborhood of $0$, so $f(x)=-x/2$ for all $x$ in some neighborhood of $0$.

Now suppose $\epsilon>0$ is such that $f(x)=-x/2$ whenever $|x|\leq\epsilon$. If $0\leq a\leq \epsilon$, the functional equation with $x=a$ and $y=-\epsilon$ then gives $$f(a+\epsilon)=-\frac{a+\epsilon}{2}.$$ That is, $f(x)=-x/2$ is also valid if $\epsilon\leq x\leq 2\epsilon$. Similarly, using $y=\epsilon$ gives that $f(x)=-x/2$ is also valid if $-2\epsilon\leq x\leq -\epsilon$.

That is, if $f(x)=-x/2$ whenever $|x|\leq\epsilon$, $f(x)=-x/2$ whenever $|x|\leq 2\epsilon$ as well. Repeating this argument over and over, we get that $f(x)=-x/2$ for all $x$.

Thus the only possibilities for $f$ are $f(x)=x$ and $f(x)=-x/2$, and you can easily check that both of these work.

$\endgroup$
3
  • $\begingroup$ Nice try! Even if using machinery which .. outguns the problem! I downvoted by accident.(and I thought I had already cancelled it. Seems I hadn't!) I will make a trivial edit so that I'll be able to cancel it. P.S.: the part where you are arguing about the cosets of the group of periods is not very clear. Could you expand it a little? (what is the equivalence relation here? why does the continuity of $g$ implies that every coset accumulates at $0$ ?). $\endgroup$
    – KonKan
    Sep 23, 2016 at 18:35
  • $\begingroup$ I've clarified that part a bit. $\endgroup$ Sep 23, 2016 at 19:12
  • $\begingroup$ Thanks for your response. As I've already said: very nice ! +1 $\endgroup$
    – KonKan
    Sep 25, 2016 at 19:49

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.